Assessment of forest encroachment using remote sensing technique. Case study: Mentigi forest reserve, cameron highlands - Mat Zin, Mohd. Hayyi (2015)
Agriculture is one of the biggest and profitable activities in Cameron Highlands, Malaysia. High quality plantation products such as tea, vegetable, fruits and flower have high demand in Malaysia. These profitable activities however have caused illegal agriculture and farming. Farmers tend to extent their farm by encroaching government lands and take advantage on any open space for illegal farming. These encroachment activities have affected forest reserve area including Mentigi Forest Reserve (MFR). This study is to identify and evaluate the encroachment activities within MFR area using multiple remote sensing datasets (SPOT 5 and IKONOS). Cadastral parcel map was used to delineate the MFR area and also provide the actual size of MFR area. Hybrid classification method was used on remote sensing image to classify the land-cover in the study area. Ground truth data from field observation were used to assess the accuracy of the classification. Results of this study showed the technique used was able to identify encroachment activities such as agriculture and development. The total encroachment area in MFR was about 2.8 ha in 2001 and has increased to about 7.3 ha in 2010. These encroachment areas represent 0.39% and 1.46% respectively. This area might be small but it may affect the forest ecosystem which can lead to hazardous natural disaster if not well monitored and managed.